Reinforcement of Bearing Capacity Foundation using Single Soil Column Method Fixed Diameter 3.2 cm with Calcium Carbide Residue (CCR) and Rice Husk Ash (RHA) Mixed Materials - Dwi Wahyuni; Ratna Dewi; Yulindasari Yulindasari; Siti Nur Indah Sari (Program Pascasarjana Universitas Sriwijaya, 2023)
Soil reinforcement method is one of the efforts to improve the technical properties of soil, such as soil bearing capacity, compressibility and permeability. The soil column method is one of the alternatives to improve physical properties by stabilization to improve soil bearing capacity. This research aims to increase the bearing capacity of the sole foundation by using the soil column method with a mixture of clay, 3% calcium carbide residue (CCR) and 12% Rice Hush Ash (RHA). This research was conducted experimentally in the laboratory using clay test specimens taken from Padamaran Village, OKI, South Sumatra Province, which were put into a test box with 1 m x 1 m x 1.4 m dimensions. The soil column modelling in this research used the soil column method. The soil column modelling in this study used a single column variation with a diameter of 3.2 cm with lengths of 40 cm, 46 cm, and 53 cm, respectively. The results are the clay foundation plate's ultimate soil bearing capacity (qu) before and after reinforcement with the soil column method. The bearing capacity of the footprint foundation plate on the largest clay soil occurs in the soil column variation with a length of 40 cm and a diameter of 3.2 cm, where the bearing capacity of the clay soil, which was originally 140 kPa increased to 21 kPa. In the experimental results of the loading test, the longer the column, the bearing capacity of the column decreases, which may have something to do with the slenderness factor of the column. The slimmer the column, the smaller the compressive strength of the column so that the tendency of the column to bend/collapse becomes greater. It happens because slender columns not only accept axial forces but also consider the addition of secondary moments due to the slenderness of the column. Then, the column cannot withstand the shear load due to the compacted clay soil around the column.